FORMING OF COMPANY REGULATIONS PT GREAT DYNAMIC INDONESIA ADJUSTABLE TO LAW NUMBER 11 YEAR 2020 CONCERNING WORK CREATION - Kelvin Kelvin; David Tan (ConCEPt - Conference on Community Engagement Project, 2022)
Policies in company regulations are important so it is necessary to update the policies in a company regulation. We can notice this when there are reforms in the arrangements in the employment cluster, namely the Omnimbus law or Law no. 11 of 2020 concerning job creation. The renewal of these regulations certainly triggers issues that affect the welfare of workers in a company, starting from the arrangement of wages, severance pay, work agreements for a certain time or a lifetime contract. Some of the problems found when carrying out this practical work activity program are the absence of renewal of policies in a company regulation, so in this case the author thinks he wants to carry out this practical work activity by providing assistance in the preparation of new company regulations and fair for employees in the company.